The Nonlinear Impact of Payment System Innovation on Financial System Stability in the ASEAN-4 Countries - Ekananda, Mahjus (UI Scholars Hub, 2022)
The increasing growth of ﬁnancial system encourages payment system innovation that can affect ﬁnancial system stability, particularly in ASEAN countries. This study explored a variety of payment system innovation, i.e. debit cards, credit cards, electronic money, and RTGS. The ﬁnancial system stability index is measured by calculating the composite indexes of non-performing loans, Z-score from ROA and CAR, share price volatility, and yield bonds. The components of the indexes are structured to reﬂect risks from the banking, stock, and bond markets. The resulting index value indicates the level of risk in the ﬁnancial system. A higher index speciﬁes a higher risk and a more vulnerable ﬁnancial system. Furthermore, it is noted that the effects of the independent variable can change according to economic conditions. The panel threshold model was applied to calculate the effects of various regimes, namely innovation, GDP, credit ratio, and stability index. The panel data were obtained from the ASEAN-4 countries (Indonesia, Malaysia, Thailand, and the Philippines) from 2012 to 2020. The panel threshold analysis shows an increase in the value of debit card, credit card, and RTGS transactions. Speciﬁcally, innovation and GDPR negatively affect the stability index. Increasing the value of payment system innovation will decrease the risk to ﬁnancial system stability in ASEAN countries. The monetary authorities of each country can implement these ﬁndings by considering the rapid development of payment system innovation and the danger it may pose to ﬁnancial system stability.